Accessing Genetic Information with Liquid Biopsies. Issue 10 (October 2015) - Cai, Xuyu; Janku, Filip; Zhan, Qimin; Fan, Jian-Bing
<x xml:space="preserve">Abstract</x> Recent scientific advances in understanding circulating tumor cells, cell-free DNA/RNA, and exosomes in blood have laid a solid foundation for the development of routine molecular 'liquid biopsies'. This approach provides non-invasive access to genetic information – somatic mutations, epigenetic changes, and differential expression – about the physiological conditions of our body and diseases. It opens a valuable avenue for future genetic studies and human disease diagnosis, including prenatal and neurodegenerative disease diagnosis, as well as for cancer screening and monitoring. With the rapid development of highly sensitive and accurate technologies such as next-generation sequencing, molecular 'liquid biopsies' will quickly become a central piece in the future of precision medicine.